Combination Therapy With Charged Particles and Molecular Targeting: A Promising Avenue to Overcome Radioresistance - Konings, Katrien; Vandevoorde, Charlot; Baselet, Bjorn; Baatout, Sarah; Moreels, Marjan (Frontiers in Oncology, 2020)
Radiotherapy plays a central role in the treatment of cancer patients. Over the past decades, remarkable technological progress has been made in the field of conventional radiotherapy. In addition, the use of charged particles (e.g. protons and carbon ions) makes it possible to further improve dose deposition to the tumor, while sparing the surrounding healthy tissues. Despite these improvements, radioresistance and tumor recurrence are still observed. Although the mechanisms underlying resistance to conventional radiotherapy are well studied, our knowledge on the impact of particle therapy on radioresistance is limited. The purpose of this review is to discuss the potential role that charged particles could play to overcome radioresistance. In order to provide a comprehensive overview, some important factors of the tumor micro-environment, such hypoxic regions and cancer stem cells, will be covered in this review together with molecular pathways that are involved in radioresistance. Finally, new lines of future research will be proposed, with a focus on novel molecular inhibitors that could be used in combination with particle therapy as a novel treatment option for radioresistant tumors.